Modelos plim para otimização de circuitos da rede de distribuição secundária de energia elétrica - Bettoni, Luiz Marcelo Michelotti (2011)
In eletric power distribution systems it is common to develop projects to improve the levels of load balancing, transformer loading and voltage drops along secondary network circuits. This paper presents Mixed Integer Linear Programming (MILP) mathematical models for adressing four technical interventions usually undertaken to achieve these improvements: load balancing, conductor changing, circuit split, and load relocation. These models comply with technical and electrical aspects and satisfy operational considerations from specialists in finding solutions that minimize the required investment for restoration of circuit levels. A simplified linear power flow method, based on the Backward-Forward Sweep (BFS), is proposed to include voltage levels constraints into the models. The combination of interventions is suggested in a proposal for integration of models by chaining solutions. To develop the MILP models the GUSEK modeling environment was created as an interface for the GLPK free solver. The models were implemented in a decision-making support tool for network improvement projects. Results are presented through case studies with data from real circuits.